Status of agricultural extension and rural advisory services worldwide: Summary report - Swanson, Burton; Davis, Kristin E. (Global Forum for Rural Advisory Services, 2014)
Extension and advisory services are a critical component of rural development, and have been shown to contribute to the reduction of hunger and poverty, increase adoption of improved technologies, and increase productivity and capacity of clientele. In the past 20 years, extension has changed from technology-focused, public services-dominated, transfer of technology approaches to a much broader scope with many different actors from the private and civil society sectors (Sulaiman and Davis 2012). Since these major changes occurred in advisory services, no global assessment has been done of the status of programmes, staffing, capacities, and financing. The last (and only) time these data were collected was in 1988 under the Food and Agricultural Organization (FAO) of the United Nations (Swanson, Farner, and Bahal 1990). The International Food Policy Research Institute (IFPRI), working in collaboration with the University of Illinois (UIUC), FAO, and the Global Forum for Rural Advisory Services (GFRAS), developed the Worldwide Extension Study database as part of the assessment of the status of agricultural extension and advisory services worldwide between 2009-2013. Also collaborating were the Inter-American Institute for Cooperation on Agriculture (IICA), the Danish Agricultural Advisory Services (DAAS), and the French Agricultural Research Centre for International Development (CIRAD). The United States Agency for International Development (USAID) supported the work. This report briefly outlines the status of public extension in these countries by region and sub-region. Much more detailed information, data, web links, and secondary documents on most countries can be found at http://www.g-fras.org/en/world-wide-extensionstudy.html.